Dogmatic thinking among university students (Journal of the College of Basic Education, 2023)
Our thinking has become accustomed to a certain pattern in looking at things and dealing with them, and this pattern is the least that can be described as being far from rationality, flexibility, and mental openness, and it often leads to rest, laziness, and perhaps dullness of mind at a time when our reality calls for it. Complex and rapidly changing, our imagination exceeds the serious and conscious stance, jumping, movement, and full readiness to face its problems. Therefore, we need a new evaluation of our thinking system that we have relied on for centuries, and we still misunderstand the thinking process, and we work according to what is dictated by conscience or emotions and emotions without That we make thought on these elements watch. (Al-Asadi, 2005, p. 21)This type of thinking is considered dogmatic thinking, as (Rokesh) indicates that the person who is characterized by dogmatic thinking is closed to the ideas he believes in, does not accept discussion or dialogue, and believes in one idea, one opinion, and one direction, and there are no points between him and others. Meeting or dialogue, and he is a rigid fanatic, and fanaticism and rigidity cannot lead to open thinking, as open thinking needs an environment of freedom, tolerance, and acceptance of the other. (Al-Shafei, 1992, p. 61).Hence, the researcher believes that dogmatism is a real problem that can undermine the entity of society and set it back, especially since university students are a mixture of different races, nationalities, and religious and intellectual sects. The opinion of the other, and that his thought is based on logic and mental evidence instead of tyranny of opinion. Therefore, the problem of the current research is to answer the following question:(Are university students characterized by dogmatic thinking).